(untitled) (Social Science Review, 2026)
This paper examines China’s ‘String of Pearls’ strategy – a phrase that was first coined by Booz Allen Hamilton in 2005 – in the Indian Ocean with a focus on India’s security concerns and its counter-strategic response, contextualized within the framework of China’s BRI. BRI, unveiled in 2013, actually represents China’s desire to improve regional connectivity and establish its dominance through infrastructure projects, particularly in the maritime and continental domains. The ‘String of Pearls’ strategy refers to China’s attempt to build a network of ports and bases along the Maritime Silk Road (MSR) – a maritime component of BRI – in the Indian Ocean Region (IOR), vis-a-vis military presence, which raises a serious security concern for India. China’s strategic investments to encircle India through this strategy are best illustrated by key locations such as Gwadar in Pakistan, Kyaukphyu in Myanmar, Hambantota in Sri Lanka, and Chittagong in Bangladesh. In response, India has taken some diverse measures to counterbalance China’s growing influence, including the ‘Neighborhood First’ policy, ‘Act East’ policy, ‘Necklace of Diamonds’ strategy, and participation in the QUAD, etc. Apart from this, India is also pursuing initiatives like Project Mausam, SAGAR, and the International North-South Transport Corridor (INSTC) to enhance its maritime security and economic ties. This study concludes by contending that, even though India has every reason to be concerned about China’s BRI-related ‘String of Pearls’, the country must actively participate in the project to avoid the ‘Thucydides Trap’, and foster regional stability, while also considering closer strategic alignment with like-minded anti-China nations (i.e., Australia, the US and Japan). Social Science Review [The Dhaka University Studies, Part-D], Vol. 42, No.2, December 2025, pp. 137-158